2013
DOI: 10.1016/j.cbi.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of discrimination between oxidized and reduced coenzyme in the aldehyde dehydrogenase domain of Aldh1l1

Abstract: Aldh1l1, also known as 10-formyltetrahydrofolate dehydrogenase (FDH), contains the carboxy-terminal domain (Ct-FDH), which is a structural and functional homolog of aldehyde dehydrogenases (ALDHs). This domain is capable of catalyzing the NADP+-dependent oxidation of short chain aldehydes to their corresponding acids, and similar to most ALDHs it has two conserved catalytic residues, Cys707 and Glu673. Previously, we demonstrated that in the Ct-FDH mechanism these residues define the conformation of the bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(99 reference statements)
0
10
0
Order By: Relevance
“…The authors showed that there is a transient covalent bond between the sulfur atom of the catalytic cysteine and the C4N atom of the nicotinamide ring, which holds the coenzyme in the active “hydride transfer” conformation in the structure of the enzyme with NADP+ (PDB entry 2O2Q). This bond was shown to be an indicator of the oxidation state of the coenzyme [10, 23]. The same adduct was predicted by quantum chemical calculations for ALDH2 [24].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The authors showed that there is a transient covalent bond between the sulfur atom of the catalytic cysteine and the C4N atom of the nicotinamide ring, which holds the coenzyme in the active “hydride transfer” conformation in the structure of the enzyme with NADP+ (PDB entry 2O2Q). This bond was shown to be an indicator of the oxidation state of the coenzyme [10, 23]. The same adduct was predicted by quantum chemical calculations for ALDH2 [24].…”
Section: Introductionmentioning
confidence: 66%
“…The mechanism, by which the enzyme differentiates the oxidation states of the coenzyme, is not fully understood. This mechanism was studied in detail by Tsybovsky and coworkers for 10-formyltetrahydrofolate dehydrogenase from Rattus norvegicus (C t -FDH) [6, 23]. The authors showed that there is a transient covalent bond between the sulfur atom of the catalytic cysteine and the C4N atom of the nicotinamide ring, which holds the coenzyme in the active “hydride transfer” conformation in the structure of the enzyme with NADP+ (PDB entry 2O2Q).…”
Section: Introductionmentioning
confidence: 99%
“…Aldehyde dehydrogenases, and in particular Aldh2, have been known to contain redox-sensitive thiol groups that are subject to oxidative inactivation (Loomes and Kitson, 1989;Moon et al, 2005;Wang et al, 2011) (Figure 4A). Recent studies on the reaction mechanism of aldehyde dehydrogenases indicated a transient covalent bond of the conserved reactive cysteine residue with the nicotinamide ring of NADP + (DiazSanchez et al, 2011;Tsybovsky et al, 2013).…”
Section: Aldehyde Dehydrogenasesmentioning
confidence: 99%
“…This residue is buried in the core of each C-terminal subunit (~15 Å from the protein surface), and accessible only via two channels that approach the sulfhydryl from opposite sides (14,19,20). One channel holds the electron acceptor, NADP + , while the other presumably provides access to the S-formylated 4-PP electron donor.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that two most distinct conformations in this spectrum of conformations are closed (where the ACP domain is associated with the dehydrogenase domain and the 4-PP group inserted into the dehydrogenase catalytic center) and fully open (the formyltransferase, ACP, and dehydrogenase domains are dissociated from each other). While the closed conformation is suggested by the necessity to bring the 4-PP S-formyl moiety in proximity with the dehydrogenase catalytic cysteine (14,19,20,35), the nature of the extended conformation is less obvious. Such an extended conformation, however, is suggested not only by the multicenter ALDH1L1 catalytic mechanisms, but also by the necessity for the ACP domain to interact with 4-PP transferase, the only enzyme in humans that adds the 4-PP to acyl carrier proteins (36,37).…”
Section: Resultsmentioning
confidence: 99%